(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article explores the prevention of acute erosive and ulcerative lesions in the upper gastrointestinal tract of patients suffering from extensive thermal burns. It discusses the high incidence of these complications, often leading to severe outcomes like bleeding and multiple organ failure. Through endoscopic research, the early development of ulcers post-burn is detailed, along with their treatment using conservative methods primarily, including the use of proton pump inhibitors like omeprazole. The study also highlights the importance of understanding the pathogenesis of these ulcers, emphasizing the role of increased acid production and delayed gastric motility in their development.